2014
DOI: 10.2147/opth.s68217
|View full text |Cite
|
Sign up to set email alerts
|

Fuchs endothelial corneal dystrophy: clinical characteristics of surgical and nonsurgical patients

Abstract: PurposeTo review the patient and clinical characteristics of patients with Fuchs endothelial corneal dystrophy (FECD).MethodsReview of records for every patient who presented to the Bascom Palmer Eye Institute between 2003 and 2009 whose visit was coded for endothelial corneal dystrophy (International Classification of Diseases, Ninth Revision [ICD9] 371.57), bullous keratopathy (ICD9 371.23), or who underwent a corneal surgery with or without cataract extraction. Demographic, clinical, and ancillary testing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Some studies assessing a relatively small study population have shown a sex predilection in female dogs; however, this finding has not been consistent across all studies . Women are reported to be at higher risk than men for developing Fuchs’ endothelial dystrophy and, as this human disorder shares many similarities to canine PCED, affected dogs have been suggested as a potential study model for the human disease . The sex distribution in our study involving 238 PCED‐affected dogs failed to show a significant sex predisposition with 40.8% female dogs and 59.2% male dogs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies assessing a relatively small study population have shown a sex predilection in female dogs; however, this finding has not been consistent across all studies . Women are reported to be at higher risk than men for developing Fuchs’ endothelial dystrophy and, as this human disorder shares many similarities to canine PCED, affected dogs have been suggested as a potential study model for the human disease . The sex distribution in our study involving 238 PCED‐affected dogs failed to show a significant sex predisposition with 40.8% female dogs and 59.2% male dogs.…”
Section: Discussionsupporting
confidence: 90%
“…7,10 Women are reported to be at higher risk than men for developing Fuchs' endothelial dystrophy and, as this human disorder shares many similarities to canine PCED, affected dogs have been suggested as a potential study model for the human disease. 6,7,39 The sex distribution in our study involving 238 PCED-affected dogs failed to show a significant sex predisposition with 40.8% female dogs and 59.2% male dogs. The age of diagnosis of 11.4 years in this study is largely consistent with previous studies showing that PCED is generally a disease of older dogs.…”
Section: Discussionmentioning
confidence: 48%
“…By contrast, human patients with endothelial decompensation from FECD typically exhibit more subtle increases in CCT of approximately 10% to 50% versus normal individuals. 33 This difference in CCT between canine CED and human FECD affected patients is likely multifactorial. First, key differences in corneal structure exist between humans and dogs.…”
Section: Discussionmentioning
confidence: 99%
“… 35 37 Second, it is likely that human patients with mild corneal edema exhibit decreases in visual acuity that prompt rapid clinical evaluation and subsequent surgical intervention. 33 By contrast, owners of dogs with canine CED are less likely to seek consultation with a veterinary ophthalmologist or choose a surgical intervention until late in the disease course due to blindness or ocular discomfort from recurrent corneal ulceration. 9 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…2. Единичные (А), множественные (B) и сливные (C) темные зоны, обнаруженные при эндотелиальной микроскопии роговицы пациентов после кератотомии Cornea guttata является предшественницей эпителиально-эндотелиальной дистрофии роговицы, которая на начальной стадии протекает бессимптомно [16,17]. Однако эндотелиальные нарушения (снижение плотности эндотелиальных клеток, полимегатизм и плеоморфизм) могут быть выявлены за несколько лет до появления у пациента развернутой клинической картины дистрофии [15][16][17].…”
Section: ;13(4):241-246unclassified